Razumna presoja in razlaga interventnih predpisov covid-19 o poslovanju sodišč - Plavšak, Nina (Podjetje in delo, 2020)
The author analyses the extent of the limitation of court operations during the COVID epidemic or the court holidays that should reasonably be necessary. To achieve the purpose of the regulation in Article 83 and 83a of the Courts Act, the following are not required: (1) the prohibition of issuing court decisions, and (2) the prohibition of service of judicial documents. In Article 83 of the Courts Act, the general prohibition of court hearings during the court holidays should be replaced by a prohibition that is not applicable if both parties agree that a hearing be held during court holidays. The reasons for delaying procedural and substantive legal deadlines due to the restrictive COVID-19 measures have ceased, as the access of parties to the court is no longer limited to the extent to justify that delay.
Keywords: court holidays; courts; COVID-19 measures; epidemije; interventni predpisi; sodišča; sodne počitnice; sodstvo; ukrepi covid-19